Complications of Anorectal Surgery : Prevention and Management - Abcarian, Herand; Cintron, Jose; Nelson, Richard (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, sate of the art review of complications related to anorectal surgical procedures old and new. As anorectal surgery has evolved throughout the decades, newer and at times unexpected complications arise as of necessity. Any surgeon not familiar with these, may be perplexed as to how to manage these specific complications and more importantly how to avoid such complications in the course of their future practice. Complications of Anorectal Surgery: Prevention and Management provides a very helpful resource for all surgeons performing anorectal surgery and will be particularly useful for general surgeons practicing in rural or small urban settings where access to a colon and rectal specialist, a large medical center or a resource medical library may be scarce or limited.
Keywords: Medicine.; Rectum -- Surgery.; Surgery.; elektronické knihy; electronic books